Laboratory manual in general microbiology - Enriquez, Gloria L. (University of the Philippines Press, 1995)
Laboratory manual that is used for instruction of introductory courses in microbiology.This manual contains exercises that covers major areas in microbiology ranging from basic concepts and techniques to more advanced skills and applications. It may be used by undergraduate students of microbiology as well as graduate students in the biological sciences and related disciplines. The techniques, procedures and materials used in each exercise are most suitable for existing local laboratory facilities and conditions.